2016
DOI: 10.1002/hep.28930
|View full text |Cite
|
Sign up to set email alerts
|

Combined magnetic resonance elastography and collagen molecular magnetic resonance imaging accurately stage liver fibrosis in a rat model

Abstract: Background & Aims Hepatic fibrosis is associated with an overproduction of matrix proteins and a pathological increase of liver stiffness. Non-invasive magnetic resonance (MR) quantification of matrix can be assessed with a collagen-binding molecular MR probe and stiffness by MR elastography, complementary techniques. This study utilizes both imaging techniques to more accurately stage hepatic fibrosis in a rat model. Methods Thirty rats with varying levels of diethylnitrosamine-induced liver fibrosis were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Ultrasound and MR‐based elastography are two promising modalities that are currently used in the clinical setting 46, 47. Our group previously compared MR elastography and EP‐3533 in a diethylnitrosamine‐induced model of rat fibrosis and found that collagen imaging was more sensitive at earlier stages of fibrosis and may provide value in this regard 22. Further comparison between MR elastography and collagen molecular imaging is thus needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound and MR‐based elastography are two promising modalities that are currently used in the clinical setting 46, 47. Our group previously compared MR elastography and EP‐3533 in a diethylnitrosamine‐induced model of rat fibrosis and found that collagen imaging was more sensitive at earlier stages of fibrosis and may provide value in this regard 22. Further comparison between MR elastography and collagen molecular imaging is thus needed.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen proportional area (CPA) and hepatic lipid vacuolization were calculated from whole‐slide scanned sections using ImageJ (National Institutes of Health). Hydroxyproline was quantified by high‐performance liquid chromatography analysis 19, 20, 21, 22…”
Section: Methodsmentioning
confidence: 99%
“…While CT can stage pulmonary fibrosis, Gd-Hyd-enhanced MRI can report locally on regions of active fibrogenesis. In the liver, Gd-Hyd-enhanced MRI can be performed in the same study as MR elastography to provide complementary measures of fibrosis and fibrogenesis, as has been shown for other molecular imaging approaches (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a gadolinium-based probe, EP-3533, has been explored in two different rodent models of liver fibrosis [185,186]. Recent studies suggest that EP-3533 may be synergistic with MR elastography, with changes in EP-3533 signal dominant in early fibrosis and MR elastography changes dominant in late fibrosis [187]. An alternative molecular imaging approach has been to develop molecular markers that specifically target hepatic stellate cells [188,189].…”
Section: Direct Molecular Imaging Probes Of Collagenmentioning
confidence: 99%